Historical and planned changes in the south Florida ecosystem - Alex Score; Charles Jacoby (EDIS)
FA127, a 5-page illustrated fact sheet by Alex Score and Charles Jacoby, describes the Kissimmee-Okeechobee-Everglades, or KOE, watershed, its past extent, changes affecting it in the last 100 years or so, and plans for the future. Published by the UF Department of Fisheries and Aquatic Sciences, November 2006.